North Korea's arms policy as an indirect security threat to Europe: How Pyongyang expands its partnerships with Moscow and Tehran - Elisabeth Suh (Stiftung Wissenschaft und Politik (SWP), 2024)
At least since Russia deployed North Korean artillery and ballistic missiles against Ukraine, it is obvious that Pyongyang fuels conflicts far beyond North-East Asia. Yet, the indirect threats that North Korea poses to Europe's security and stability have developed a new quality: Pyongyang is actively supporting Russia's and Iran's security policy goals by supplying ammunition for fighting the wars in Ukraine and the Middle East. North Korea has thereby raised its strategic value for Moscow and Tehran. This allows Pyongyang to expand and exploit these partnerships in service of its own interests and to jointly expand and secure supraregional networks for violating sanctions and engaging in smuggling. The EU needs more information and international cooperation in order to understand Pyongyang's practices and to identify and use opportunities to shape the current situation.
Keywords: 320; artillery; ballistic missiles; Russia; Iran; war in Ukraine; war in the Middle East; violating sanctions; smuggling; nuclear proliferation; Multilateral Sanctions Monitoring Team; NATO